PENGARUH PEMBERIAN EKSTRAK DAUN KELOR DAN KONSENTRASI PUPUK GREEN IONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) - Budi Alhadi; Mawardiana Mawardiana; Erni Anjani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This study aims to determine the effect of Moringa leaf extract and green ionic concentration on the growth and yield of peanut plants. This research was conducted in the experimental garden of the Faculty of Agriculture, Jabal Ghafur University, which took place from 18 October to 30 December 2019. This study used a factorial randomized block design consisting of 2 factors. The first factor, Moringa leaf extract (E1: 1.44 ml L-1 water, E2: 2.88 ml L-1 water, E3: 4.32 ml L-1 water) and the second factor, the concentration of ionic green manure (I1: 2 ml L-1 water, I2: 4 ml L-1 water and I3: 6 ml L-1 water) The parameters observed were plant height, number of pods planted, weight of wet pods per plot, weight of dry pods per plot. and yield per hectare. The results showed that the application of Moringa leaf extract and green ionic fertilizer concentration had no significant effect on plant height, number of pods planted, wet pod weight per plot, dry pod weight per plot and yield per hectare, and there was no interaction with all observation parameters.Keywords : Moringa leaf extract, green ionic fertilizer and peanuts